Immune thrombocytopenic purpura during a dengue outbreak: A dynamic masquerader (Indian Journal of Case Reports, 2019)
In this age of enhanced diagnostics and improved turnaround time, immune thrombocytopenic purpura (ITP), a disease primarily diagnosed by exclusion, is expected to be straightforward to diagnose. However, during a full-fledged dengue outbreak, the health-care system can be overwhelmed, and as a result, ITP can be underdiagnosed. The clinician should be aware of the various imitations that ITP can present with. Various clinical indicators have to be kept in mind while dealing with such an outbreak to avoid unnecessary health-care expenditure and prolonged hospital stays. In this case series, we present two patients diagnosed to have ITP during the dengue outbreak, each unique in its presentation and course, demonstrating the multiple patterns ITP can present itself.